Emanuel AME Church: Christianity as resistance. Issue 4 (5th December 2018) - Williams, Reggie L.
Abstract: The struggle against white supremacy in the United States is a battle with deadly forces deep within the heart of the nation. For many caught within the crosshairs of those forces, the struggle also becomes a theological problem of evil that includes deep divisions over the role of the black church in the conflict. The terrorist act that took the lives of nine church members during a Wednesday evening Bible study at Mother Emanuel AME Church in South Carolina, in June of 2015, placed the struggle before us in high definition, and also demonstrated the historical role of black Christian worship in the face of white racist Christianity. The black church inspires life‐giving alternatives to the death‐dealing work of racism within a nation that is religiously, and politically, devoted to white supremacy.